Komunikasi Politik di Komunitas Virtual - Satria Kusuma (Atma Jaya Indonesia Catholic University, Jakarta, 2014)
Political communication is aesthetic especially the mass-mediated political communication. By exploiting political communication’s aesthetic properties similar to a game, political leaders use the channel to generate a movement of people by using political symbolism. One of the mass channels is the Internet which elevates individuals out of the isolation created by the walls of the old media-especially when these walls are reinforced in the context of urban culture. In the information society, people increasingly interact with computer screens developing face-to-screen relationships rather than face-to-face. The 'Age of Internet' is identical with the opportunity to build virtual communities in which we participate with people from all over the world. Computer-mediated communication in the traditional type of decision-making activities such as voting characterizes the type of participatory democracy. This review summarizes that Indonesia, which is ranked the world's fifth with the highest number of Twitter accounts and become the country with the highest Twitter penetration rates in the world, has the highest potential target of the presidential candidates in Indonesia. The majority of Twitter users in Indonesia are 16-20 years old, comprising one-third of the 187 million voters in the 2014 presidential election.